Fatwa Perspektif Al-Shatibi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The purpose of this research is to find out Al-Shatibi's fatwa perspective. This research uses a type of library research. The research carried out is descriptive in nature where the researcher collects words instead of a series of numbers for this research, which in essence these words can provide an overview or present existing problems and solutions. The data analysis used is content analysis. A fatwa is a response to a question asked by a fatwa seeker (mustafti>). Whether questions are asked by individuals, institutions or collectives. In general, fatwas are issued in response to questions about current shari'ah problems. The legal basis (the arguments for the enactment of a fatwa are as stated in the Qur'an). The position of a fatwa in the Islamic legal system is very important considering that social problems are increasing day by day and becoming more complex. Moreover, a fatwa is an explanation of sharia law for certain problems which are not all people can understand it. The ways to give fatwa according to al-Shatibi are divided into three: a). With the words (bi al-Qaul)., b). By deeds (bi al-Fi'il), c). and determination (bi al-Iqrar). As for determining a fatwa with words, this is the model of determining that is considered the most widely used. by a mufti>. Meanwhile, determining a fatwa by deeds occupies the position of the model of determining a fatwa by words because this second model is an explanation (al-Musrih of the first model of determining a fatwa. The concept of al-Sha>tabi>'s fatwa is a theory that was born in his time with a portrait of life that is of course different from today. Therefore, there are three things which – according to researchers – still leave